The inference-boundary model reinterpreting theme and rheme - Leong, Ping Alvin (2013)
The Hallidayan notions of theme and rheme pose an interesting challenge to linguists in their attempts to pin them down more specifically. This paper argues that since the thematic structure of the clause organises it as a message, a useful starting point in theme–rheme research is an understanding of how clausal messages are typically processed by language users. A cognitive psychological model is constructed in this paper. It views theme as an element that generates a boundary of acceptability within which it is permissible for the rheme to occur. Underlying the thematic structure of the clause is a principle dictating that the theme must be acceptably developed by the rheme. This principle forms the basis of a test to identify and delimit the thematic head.